Phylogeny based on ultra-conserved elements clarifies the evolution of rails and allies (Ralloidea) and is the basis for a revised classification. Issue 4 (16th July 2021) - Kirchman, Jeremy J; Rotzel McInerney, Nancy; Giarla, Thomas C; Olson, Storrs L; Slikas, Elizabeth; Fleischer, Robert C
Abstract: The rails (Family Rallidae) are the most diverse and widespread group in the Gruiformes. Their extensive fossil history, global geographic distribution, and tendency to rapidly evolve flightless species on islands make them an attractive subject of evolutionary studies, but the rarity of modern museum specimens of so many rail species has, until recently, limited the scope of molecular phylogenetics studies. As a result, the classification of rails remains one of the most unsettled among major bird radiations. We extracted DNA from museum specimens of 82 species, including 27 from study skins collected as long ago as 1875, and generated nucleotide sequences from thousands of homologous ultra-conserved elements (UCEs). Our phylogenetic analyses, using both concatenation and multispecies coalescent approaches, resulted in well-supported and highly congruent phylogenies that resolve the major lineages of rails and reveal several currently recognized genera to be polyphyletic. A fossil-calibrated time tree is well-resolved and supports the hypothesis that rails split into 2 major lineages (subfamilies Himantornithinae and Rallinae) ~34 mya, but clade age estimates have wide confidence intervals. Our results, combined with results of other recently published phylogenomics studies of rails and other Gruiformes, form the basis for a proposed classification of the Rallidae that recognizes 40 genera in 9 tribes. Lay Summary: Rails are a diverse, globally distributed group of birds that are of great interest to ornithologists that study fossil birds and the evolution of flightless species on islands. But because so many rail species are rare or extinct, studying rail evolution using genomic data requires that DNA be obtained from very old museum specimens. We extracted DNA from museum specimens, including study skins of rare and extinct species collected as long ago as 1875, and generated DNA sequences from thousands of genes. The DNA-based phylogeny indicates that rails underwent an initial split into 2 groups ~34 mya, and that 9 major extant rail lineages have evolved since then. Our genetic analyses clarify the relationships of some enigmatic species that have not been studied with DNA before and are the basis for a revised taxonomic classification of rails.